Tata Kelola Perusahaan, Keuangan, Merger dan Akuisisi, dan Efisiensi Modal Manusia Sebagai Variabel Moderasi - Chandra, Budi; Seli, Seli (E-Jurnal Akuntansi, 2022)
This study aims to determine the effect of corporate governance and finance on mergers and acquisitions and to use human capital efficiency as a moderating variable. This research theoretically uses the theory of corporate control. The research sample is companies that carry out merger and acquisition activities and have been listed on the IDX in 2017-2021. The analytical method used was logistic regression and moderated regression analysis (MRA). The results showed that the size of the board of directors, institutional shareholders, and foreign ownership had a significant positive effect on mergers and acquisitions. Human capital efficiency is able to moderate the relationship between institutional shareholders and cash dividends on mergers and acquisitions. Keywords: Merger and Acquisition; Corporate Governance; Human Capital Efficiency